A blunted diurnal cortisol response in the lower educated does not explain educational differences in coronary heart disease: Findings from the AGES-Reykjavik Study. (February 2015) - Groffen, Daniëlle A.I.; Bosma, Hans; Koster, Annemarie; von Bonsdorff, Mikaela B.; Aspelund, Thor; Eiriksdottir, Gudny; Penninx, Brenda W.J.H.; Kempen, Gertrudis I.J.M.; Kirschbaum, Clemens; Gudnason, Vilmundur; Harris, Tamara B.
Abstract: Lower educational attainment generally is a strong predictor of coronary heart disease (CHD). The underlying mechanisms of this effect are, however, less clear. One hypothesis is that stress related to limitations imposed by lower socioeconomic status elicits changes in hypothalamic-pituitary-adrenal axis functioning, which, in turn, increases risk of CHD. In a large cohort study, we examined whether educational attainment was related to risk of fatal and non-fatal CHD and the extent to which salivary cortisol mediated this relation independent of potential confounders, including lifestyles. Data came from 3723 participants aged 66 through 96 from the Age, Gene/Environment Susceptibility (AGES) – Reykjavik Study. Between 2002 and 2006, data were collected using questionnaires and examinations including morning and evening salivary samples. Hospital admission records and cause of death registries (ICD-9 and ICD-10 codes) were available until December 2009. Linear regression and Cox proportional hazards analyses were performed. Even after adjustment for potential confounders, including lifestyle, persons with lower educational attainment showed a blunted cortisol response and also greater risk of incident CHD. However, our data did not support the role of cortisol as a mediator in the association between education and CHD in an older sample (192). Highlights: We assessed whether salivary cortisol mediated the relation between education and heart disease. Lower education was associated with a blunted cortisol response and greater risk of heart disease. Educational differences in heart disease were not explained by differences in cortisol response.